Ottoman craft guilds and silk-weaving industry in İstanbul - Turna, Nalan. (Thesis (M.A.) - Bogazici University. Institute of Social Sciences, 2001., 2001)
This thesis examines the Ottoman craft guilds and silk-weaving industry in İstanbul. For this study, I have used both primary and secondary sources and conducted research in the Prime Ministry Archives in İstanbul. In the archives, I mainly used the Cevdet, İradeler, Dahiliye, Hatt-ı Humayun, Meclis-i Vukela Mazbataları and Yıldız classifications. This thesis consists of six chapters. Chapter 1 provides an historical background and investigates the debates regarding the origin of Ottoman craft-guilds. Chapter 2 examines the significance of the esnaf ceremonies as a source of solidarity and the participation of the esnaf in public processions. Chapter 3 explores the organization ofthe guilds and the central government regarding the internal affairs of the guilds. Chapter 4, 5, and 6 examines how Ottoman craft guilds changed particularly during the eighteenth and nineteenth century. Chapter 4 focuses on the guilds in a broader context and discusses the incorporation of the Ottoman Empire into the European world economy, as well as the "decline" debates concerning the handicraft industries, central government's response to economic changes, and the early attempts for industrialization. Chapter 5 demonstrates the impact of the internal factors as to the. changes in Ottoman guilds. Chapter 6 focuses on the silk guilds in istanbul as a case study and examines the central government's attempts to control the distribution of silk in order to secure its revenue from the guilds and maintain the provisioning of istanbul. The last chapter, in conclusion, pictures silk industry in İstanbul, central government and its attempt to protect to protect the esnaf, which all served to legitimize the power besides the other functions.
Keywords: Guilds -- Turkey -- History.; Silk industry -- Turkey -- History.